2019
DOI: 10.1016/j.quaint.2017.10.049
|View full text |Cite
|
Sign up to set email alerts
|

A functional approach to the use of the earliest blade technology in Upper Paleolithic Hokkaido, northern Japan

Abstract: To understand the behavioral significance of the emergence and proliferation of blade technology in the northeastern Asian Upper Paleolithic, this paper explores the function of the earliest blade technology in Hokkaido, northern Japan, through an integrated analysis of edge morphology and use-wears on blade tools from the Last Glacial Maximum (LGM) assemblage of Kawanishi C. Although varied edge morphologies (i.e., straight, convex, concave, denticulate) have been distinguished, the results of use-wear analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…In recent years, it has been shown that there were hunter-gatherers in Hokkaido during the Bølling-Allerød who produced and used potteries but did not use microblades [27,89,90]. From the excavation at the Taisho-3 site in eastern Hokkaido, a lithic assemblage composed mainly of small obsidian bifacial points associated with potteries has been discovered ( Figure 5).…”
Section: Techno-complex With Potteries In the Terminal Pleistocenementioning
confidence: 99%
See 4 more Smart Citations
“…In recent years, it has been shown that there were hunter-gatherers in Hokkaido during the Bølling-Allerød who produced and used potteries but did not use microblades [27,89,90]. From the excavation at the Taisho-3 site in eastern Hokkaido, a lithic assemblage composed mainly of small obsidian bifacial points associated with potteries has been discovered ( Figure 5).…”
Section: Techno-complex With Potteries In the Terminal Pleistocenementioning
confidence: 99%
“…The Taisho-3 site is located on a slightly elevated terrace that forms a natural embankment adjacent to a river ( Figure 6). Just below the stratum containing the cultural horizon during the terminal Pleistocene is a gravel layer that was formed by river flooding; thus, human activity was conducted in a riverbed-like environment [90]. Unlike the Taisho-3 site, almost all other sites where microblade assemblages have been discovered are located on river terraces at a distance from rivers.…”
Section: Techno-complex With Potteries In the Terminal Pleistocenementioning
confidence: 99%
See 3 more Smart Citations